Influence of Glutathione and Glutathione S-transferases on DNA Interstrand Cross-Link Formation by 1,2-Bis(methylsulfonyl)-1-(2-chloroethyl)hydrazine, the Active Anticancer Moiety Generated by Laromustine - Penketh, Philip G. (American Chemical Society, 2014)
[Image: see text] Prodrugs of 1,2-bis(methylsulfonyl)-1-(2-chloroethyl)hydrazine (90CE) are promising anticancer agents. The 90CE moiety is a readily latentiated, short-lived (t(1/2) ∼ 30 s) chloroethylating agent that can generate high yields of oxophilic electrophiles responsible for the chloroethylation of the O-6 position of guanine in DNA. These guanine O-6 alkylations are believed to be responsible for the therapeutic effects of 90CE and its prodrugs. Thus, 90CE demonstrates high selectivity toward tumors with diminished levels of O(6)-alkylguanine-DNA alkyltransferase (MGMT), the resistance protein responsible for O(6)-alkylguanine repair. The formation of O(6)-(2-chloroethyl)guanine lesions ultimately leads to the generation of highly cytotoxic 1-(N(3)-cytosinyl),-2-(N(1)-guaninyl)ethane DNA interstrand cross-links via N(1),O(6)-ethanoguanine intermediates. The anticancer activity arising from this sequence of reactions is thus identical to this component of the anticancer activity of the clinically used chloroethylnitrosoureas. Herein, we evaluate the ability of glutathione (GSH) and other low molecular weight thiols, as well as GSH coupled with various glutathione S-transferase enzymes (GSTs) to attenuate the final yields of cross-links generated by 90CE when added prior to or immediately following the initial chloroethylation step to determine the major point(s) of interaction. In contrast to studies utilizing BCNU as a chloroethylating agent by others, GSH (or GSH/GST) did not appreciably quench DNA interstrand cross-link precursors. While thiols alone offered little protection at either alkylation step, the GSH/GST couple was able to diminish the initial yields of cross-link precursors. 90CE exhibited a very different GST isoenzyme susceptibility to that reported for BCNU, this could have important implications in the relative resistance of tumor cells to these agents. The protection afforded by GSH/GST was compared to that produced by MGMT.